Type species designation for the genus Rhagonycha Eschscholtz, 1830 (Coleoptera, Cantharidae) - Grosso-Silva, José Manuel; Alonso-Zarazaga, Miguel A.; Da Silva, Rubim M. Almeida (Zootaxa, 2013)
The Principle of Typification, defined by Chapter 13 of the International Code of Zoological Nomenclature (I.C.Z.N., 1999), from here on referred as “Code”, determines in Article 61.1. that each nominal taxon in the family, genus or species groups has actually or potentially a name-bearing type whose fixation provides the objective standard of reference for the application of the name it bears.